Aquaporin-based membranes made by interfacial polymerization in hollow fibers: visualization and role of aquaporin in water permeability - Sharma, Loveena (2022)
Aquaporins are water channel proteins with high permeability and solute rejection, making them ideal components for the preparation of desalination biomimetic membranes. In one strategy, E. coli aquaporin Z (AqpZ) proteoliposomes are immobilized in a polyamide layer formed by interfacial polymerization at the inner surface of hollow ﬁbers. However, once polymerization occurs, the system is almost a black box where it is difficult to disentangle the relative contribution to performance of (i) water permeation through AqpZ channels and (ii) the possible modification of the properties or structure of the polymer layer by the mere presence of protein and lipid. Indeed, the fate of protein and lipid once the polymer is formed, and how much of it is actually used, is under debate. Also, the performance of these modules has been reported to be stable over several months. This is intriguing because of the expected degradation of functional AqpZ and lipid with time. Herein, we used lipid and AqpZ, both fluorescently labeled, to unequivocally localize both components only at the inner surface of the hollow fibers. To characterize module performance, we tested about 30 half-inch modules containing five hollow fibers each. Those reconstituted with wild type AqpZ produced higher permeability (∼8.5 ± 0.9 LMH/bar) than those reconstituted with AqpZ mutant (R189A) (∼5.6 ± 1.7 LMH/bar) or lipid-only liposomes (3.7 ± 1.1 LMH/bar). However, while these differences are significant, they are smaller than expected from the comparison of relative permeabilities of membranes incorporating wild-type AqpZ, R189A mutant and only-lipid. In addition, we show that in a five-month long experiment, performance of two of these modules showed only minor deterioration, if any, which is not consistent with the observed rapid degradation of proteoliposomes at room temperature. Overall, these data obtained in this set-up suggests that although both AqpZ and lipid are localized at the inner of the hollow fibers, they mainly behave as additives that modify the properties of the robust polyamide layer. A small contribution of AqpZ channel activity to module performance is possible, but to be significant it would require full coverage and a higher protein density in the proteoliposomes, which at present cannot be achieved in the current protocol.